Analisis Jalur Kritis Pada Proses Pengadaan Jasa Konstruksi Paket 1 Pekerjaan Konservasi Pantai Candidasa Pinjaman JICA - Damayanti, Desak Putu; Ciptadi, Rian; Sandra, Deby (Ikatan Fungsional Pengadaan Indonesia, 2025)
The procurement of international construction services is the process of procurement of goods and/or services that have high complexity. This paper aims to explored the experience of the 58 Selection Working Group of the Construction Services Selection Implementation Center (BP2JK) for the Bali Region in facing critical path in the process of procurement of international construction services which is funded from Japan's official development assistance (ODA). This study can be categorized as a qualitative-evaluative study. The data analysis carried out is a simple correlation analysis, to see the relationship between the stages of construction service procurement and the duration of the implementation of construction service procurement. The stages of procurement of construction services that result in an extension of time can be used as one of the indicators of critical stages, which need to be anticipated in the future. The critical point in the process of procurement of international construction services can be very different from the process of procurement of goods and/or services sourced from the Indonesian Local Budget financing. The results of the analysis of the critical path show that the critical point of the construction service procurement process in this study occurs in the process of clarification, review, and approval from JICA. The complexity of the work and the competence of the Working Group are the main indicators that can have a negative or positive effect on the smooth process of procurement of construction services. This paper is expected to be one of the references related to the process of procuring international construction services sourced from ODA Loan Japan. Keywords: ODA Loan JICA, critical route, procurement of international construction services